Functional results of treating closed displaced femoral shaft fractures using elastic nails in children (6-12 years old). - يوسف, علي (Tishreen University Journal -Medical Sciences Series, 2024)
Objective of the study: To study the functional results of surgical treatment of femoral shaft fractures in children, which achieves healing quickly and with fewer complications. Materials and methods: The study included 25 children who visited Tishreen University Hospital between the years 2021-2022 and who underwent surgical treatment using flexible intramedullary nails. The patients were followed up clinically and radiologically after surgery during specific periods until complete healing. Results: The study was conducted on 25 patients. Most of them were males, 18 (72%), and the number of females was 7 (28%). Most of the injuries in children were caused by falls, 20 (80%), and the rest of the injuries were the result of a traffic accident, 5 (20%). The patients were followed up Clinically and radiologically after surgery, the study reached significant functional and radiological results regarding healing of fractures. Conclusion: The study concluded that it is of great importance to use intramedullary rods in the treatment of hip fractures because of the positive results it achieves and reduces complications.